Sintomas de deficiências de macronutrientes em melancieira - Costa, Leonardo Correia [UNESP]; Carmona, Victor Manuel Vergara [UNESP]; Filho, Arthur Bernardes Cecílio [UNESP]; Nascimento, Camila Seno [UNESP]; Nascimento, Carolina Seno [UNESP] (Lepidus Tecnologia, 2017)
Improper handling of lime and fertilizer can trigger nutritional disorders. This study aimed at describing and depicting the evolution of the symptoms of nutrient deficiencies in watermelon when induced in the fruiting stage, and determining the leaf content in the organ and at the time the symptom was visualized. The experiment was in hydroponics. The symptoms of N and Ca deficiencies were the first to be observed. Nitrogen deficiency caused cessation of growth, inhibition of lateral rods, general chlorosis and necrosis in older leaves. Symptoms of P deficiency first appeared in old leaves with chlorotic and wrinkled areas, which later progressed to necrosis. K deficiency caused marginal chlorosis in older leaves, progressing to the entire limb and evolving to necrosis. With calcium deficiency, the new leaves were deformed, with marginal chlorosis and necrosis, curved edges down, thick leaf blade, wrinkled and necrosis in meristems. The Mg omission initially caused symptoms of internerval chlorosis in old leaves, progressing to off-white and necrotic tissues. The levels of N, P, K, Ca and Mg in the leaf and on the occasion of deficiency were 9.7; 1.4; 7.1; 1.8 to 1.8 g kg-1, respectively.
Symptoms of deficiencies macronutrients in watermelon
Keywords: Citrullus lanatus; Mineral nutrition; Nutritional diagnosis